Overview of the ukrainian pharmaceuitical market of medications for periodontal diseases treatment in order to obtain a new dental product - I. Y. Borisyuk; L. M. Unhurian; N. S. Fizor; O. I. Bielyaieva; А. V. Zamkovaya (The State Expert Center of the Ministry of Health of Ukraine, 2020)
Oral diseases occupy the leading position among common disorders. The etiological factors of the inflammatory processes of the oral cavity can be some general disturbances of the body. Today, the topical medications are important component of the treatment and prophylactic measures of range of pathological conditions in dental practice. Among this type of medicines widely used herbal preparations, which are known for their broad spectrum of activity. The aim of the research was to scrutiny the treatment methods for OD, to study the topical medications assortment of the pharmaceutical market of used in pharmacotherapy of OD with a view to further developing the dosage form and determining the feasibility of its use in the apitherapy of OD and the possibility of occupying it with certain market niche. The data from official information sources, in particular, the List of registered drugs approved for use in Ukraine as of 01. 01. 2019 were used as the objects of study. Market analysis was carried out using the ATC classification system (Anatomical Therapeutic Chemical) taking into consideration international non-patented and trade names, dosage forms, country of manufacture. Statistical, graphic, logical and marketing studies were conducted during the work. Information was used to determine the assortment of the modern pharmaceutical market of drugs that can be used in pharmacotherapy of OD, was the order of the Ministry of Health of Ukraine No. 566 dated 11. 23. 2004. «On approval of protocols for the provision of medical care in the fields of "orthopedic dentistry", "therapeutic dentistry", "surgical dentistry", "orthodontics", "pediatric therapeutic dentistry" and "pediatric surgical dentistry"». According to the official website of the SEC of the Ministry of Health of Ukraine as of 01. 01. 2019, 76 drugs were registered as the A01A group and 59 drugs under trade names. According to the АТС classification system major topical medications belong to group A01A. The share of domestic drugs prevails over foreign ones and amounts to 60.5%. Attention was drawn to the limited range of drugs from beekeeping products, whose share is only 6.6%. It has been found that the production of original propolis-based drugs at pharmaceutical enterprises of Ukraine with a sufficient raw material base is topical issue of pharmacy.